The Gallipoli Campaign (London)
vi, 224 sayfa
Keywords: “The war against the Ottomans, on Gallipoli, in Palestine and in Mesopotamia, was a major enterprise for the Allies with important long-term geo-political consequences. The absence of a Turkish perspective, written in English, represents a huge gap in the historiography of the First World War. This timely collection of wide-ranging essays on the campaign, drawing on Turkish sources and written by experts in the field, addresses this gap. Scholars employ archival documents from the Turkish General Staff, diaries and letters of Turkish soldiers, Ottoman journals and newspapers published during the campaign, and recent academic literature by Turkish scholars to reveal a different perspective on the campaign, which should breathe new life into English-language historiography on this crucial series of events“--